Effects of Audit Committee Monitoring and Independence on Bank Performance: Evidence from Emerging Market - Md. Adnan Ahmed (Global Academy of Business Studies, 2026)
Purpose: This study explores whether audit committee monitoring intensity and independence influence the performance of listed commercial banks. Research Methodology: Tobin’s Q is used as the primary market-based measure, and Return on Assets is used as an alternative indicator. We examine two core governance variables: the lagged number of audit committee meetings and the lagged proportion of independent directors on the audit committee (ACIND). Based on panel data for listed commercial banks over 24 years, the study applies Panel-Corrected Standard Errors and Fixed Effects models to evaluate the connection between audit committee characteristics and firm performance. Results: The results show that both audit committee monitoring intensity and independence are negative and statistically significant determinants of performance across model specifications. More frequent audit committee meetings and higher committee independence are associated with lower Tobin’s Q. The robustness analysis using ROA confirms similar negative effects on accounting performance. Conclusions: The findings suggest that, in the banking context, greater audit committee monitoring and independence may reflect reactive responses to underlying risk and poor performance rather than proactive, value-enhancing governance. Limitations: This study was conducted only on banks. Other industries can be incorporated to generalize these findings. Contributions: This study highlights the importance of oversight quality, director expertise, and institutional context in shaping governance effectiveness.